Gendered attitudes and expectations towards women and men working in Icelandic preschools - Axelsdóttir, Laufey; Pétursdóttir, Gyða Margrét (Menntavísindasvið Háskóla Íslands, 2015)
The World Economic Forum (2013) annually reports on the status of the global gender gap in 136 countries (p. 6). According to the 2013 report Iceland is the country with the narrowest gender gap in the world (p. 16). Even though the situation concerning equal status between men and women is good compared with many other countries, there are still issues that need to be improved. Gender segregation in the labour market is high, women do not have the same accessibility to management positions as men, and there is still a gender pay gap (p. 220). Preschool teaching is a low-paying job (Þórdís Þórðardóttir, 2012b, p. 68 and 79), and the majority of preschool teachers are women. In 2012, 94% of preschool employees in Iceland were women (Hagstofa Íslands, 2013c), and about 98% of those studying to become preschool teachers (Hagstofa Íslands, 2013b). Qualified preschool teachers were only about 33% of preschool employees in 2013 (Hagstofa Íslands, 2013d). The aim of the article is to examine how ideas about masculinity and femininity influence men and women who work in two preschools in Iceland. Attitudes of both qualified preschool teachers and unqualified staff are taken into account in order to get a comprehensive view of the status of equal rights between men and women in the preschools. Connell´s concept of hegemonic masculinity and emphasized femininity were applied to explore gender relations in the preschools. The position of women and men in Icelandic preschools has not been studied this way before. This article seeks to answer the following question: How do ideas about femininity and masculinity influence the approaches of women and men working in preschools, and how do these ideas affect expectations towards them? Qualitative methods were used, and data was gathered during the 2011–2012 school year. Data was collected in two preschools, consisting of ten interviews and two participant observations. Five interviews were conducted in each preschool, four with women and one with a man. Their job experience ...